2016
DOI: 10.1111/edt.12285
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the tooth staining potential of endodontic materials in a bovine tooth model

Abstract: The presence of bismuth oxide in calcium silicate cements was not shown to be a reliable predictor for tooth discoloration. Antibiotic pastes without tetracycline derivatives do not guarantee the color stability of teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 37 publications
4
43
1
Order By: Relevance
“…Previous studies have demonstrated that pure calcium hydroxide caused no visible discoloration in any experimental time [1, 25]. In the present study, the Vitapex, composed of calcium hydroxide and iodoform, and calcium hydroxide paste thickened with zinc oxide showed Δ E 00 ∗ values exceeding the perceptibility threshold [14]. This color change caused by Calen + ZO may be attributed to the zinc oxide present in its formula, while, in the Vitapex group, it may be related to the production of a yellowish-brown discoloration generated by iodoform, compromising the aesthetics [26].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Previous studies have demonstrated that pure calcium hydroxide caused no visible discoloration in any experimental time [1, 25]. In the present study, the Vitapex, composed of calcium hydroxide and iodoform, and calcium hydroxide paste thickened with zinc oxide showed Δ E 00 ∗ values exceeding the perceptibility threshold [14]. This color change caused by Calen + ZO may be attributed to the zinc oxide present in its formula, while, in the Vitapex group, it may be related to the production of a yellowish-brown discoloration generated by iodoform, compromising the aesthetics [26].…”
Section: Discussionsupporting
confidence: 47%
“…Due to the number of dentinal tubules, bovine teeth have no significant difference compared to human teeth [13]. For the assessment of discoloration, enamel-dentine blocks were used in order to standardize the thickness of the dentine in contact with the material, as well as the size of the cavity and the amount of material employed [1, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that TAP with cefaclor induced tooth discoloration (10,17). Ackay et al (10) and Santos et al (16) claimed that double antibiotic paste placed in the root canal was not the cause of tooth discoloration; this was in contrast with findings by Dettwiler et al (14), who used enamel-dentin blocks as samples, which did not fully correspond to real teeth. Calcium hydroxide exhibited no staining potential in the reviewed studies (8-10,16), but it was noted that ApexCal (Ivoclar Vivadent, Schaan, Liechtenstein), which is a calcium hydroxide-based product with bismuth carbonate, showed the ability to discolor teeth (9).…”
Section: Discussionmentioning
confidence: 95%
“…Table 1 shows information regarding the analyzed materials, irrigants, tooth type, sample preparation method, measurement time, measurement method, and discoloration (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Figure 2 presents delta E values from studies that included its value in results (8,9,12,14,16,17); however, not all studies included numeric delta E values. A statistical analysis could not be performed because of different parameters used by reviewed studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation